Tinjauan Lembaga Peradilan Adat Minangkabau Dalam Sistem Peradilan Di Indonesia (Kajian Terhadap Peraturan Daerah Nomor 7 Tahun 2018 Tentang Nagari Di Provinsi Sumatera Barat) - Adeb Davega Prasna (Program Studi Akuntansi IKOPIN, 2022)
Overview of the Minangkabau Adat Court in the Indonesian Judicial System (Review of Regional Regulation Number 7 of 2018 concerning Nagari in West Sumatra Province). This study aims to analyze the position and function of the Customary Courts in the West Sumatra Regional Regulation No. 7 of 2018. In addition, this study also analyzes the existence of adat court institutions in the context of reforming the Indonesian constitutional system. This study uses a library research method with a qualitative approach. This study also uses a historical approach by examining the history of the position of the adat court in Indonesia. The results of the study show that the adat court institution in Indonesia has existed for a long time, even before the colonial period. After that, the existence of adat court institutions in Indonesia was still recognized until 1951. After the issuance of Emergency Law no. 1 of 1951, all adat court institutions in Indonesia were abolished and their existence was not recognized. The Regional Government of West Sumatra gave birth to Regional Regulation No. 7 of 2018 concerning Nagari which regulates autonomous Nagari government based on the Undang-Undang Desa and Undang-Undang Pemerintahan Daerah. The most interesting thing about this Perda is the inclusion of provisions on the Nagari Court which aims to resolve customary civil problems that arise in the community. The existence of this adat court institution should be legally and legally recognized. This recognition can be done by including the customary court as a special judicial institution under the Supreme Court, or its existence is recognized as an alternative institution for resolving cases outside the court.